DANCE AND MUSIC: FUNK AS BODY LANGUAGE IN PHYSICAL EDUCATION LESSONS (Fiep Bulletin - online, 2017)
Discussing socio-cultural theme within the sports area means to recognize that education is not dissociated from thesociety and its culture, since individual experiences cannot be ignored as learning. In this sense, it is intended, in this paper, tounderstand how the funk dance, as a cultural element, contributes to meanings for the further development of the students duringthe physical education lessons. Psychological, cognitive, motor benefits are among those which can benefit students throughdance activities; this is the reason why they have become part of the content of this subject. However, dances are mostly used forextracurricular activities or special dates. The Brazilian Physical Education Parameters, which are the reference for nationaleducation, guiding and assisting teachers, highlight the importance of the dance in lessons as well as its advantages for thestudents.